2019
DOI: 10.1002/mrm.27633
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of synovial tissue volume in knee osteoarthritis using a semiautomated MRI‐based quantitative approach

Abstract: Purpose Synovitis is common in knee osteoarthritis and is associated with both knee pain and progression of disease. Semiautomated methods have been developed for quantitative assessment of structure in knee osteoarthritis. Our aims were to apply a novel semiautomated assessment method using 3D active appearance modeling for the quantification of synovial tissue volume (STV) and to compare its performance with conventional manual segmentation. Methods Thirty‐two sagitta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…DCE-MRI biomarkers derived from semiautomatic segmentation performed better than those derived from manual segmentation across the majority of assessment domains. Previous studies have demonstrated reduction in time taken for analysis with semiautomatic approaches but with similar repeatability and reproducibility to manual approaches [ 28 , 29 ]. One plausible explanation for the demonstrated superiority of our semiautomatic approach is the fact that we used shuffle subtraction prior to our thresholding step, in contrast to approaches which attempt to threshold from the post-contrast images alone.…”
Section: Discussionmentioning
confidence: 99%
“…DCE-MRI biomarkers derived from semiautomatic segmentation performed better than those derived from manual segmentation across the majority of assessment domains. Previous studies have demonstrated reduction in time taken for analysis with semiautomatic approaches but with similar repeatability and reproducibility to manual approaches [ 28 , 29 ]. One plausible explanation for the demonstrated superiority of our semiautomatic approach is the fact that we used shuffle subtraction prior to our thresholding step, in contrast to approaches which attempt to threshold from the post-contrast images alone.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding DCE measures Axelsen et al assessed responsiveness to treatment and reliability of DCE MRI in 10 rheumatoid arthritis knee joints on a 1.5 T system and reported high intra-and inter-reader reliabilities of the dynamic parameters with ICC values ranging between 0.96 to 1.00 [24]. Using a semi-automated method for synovial volume assessment Perry et al described excellent intraobserver (ICC 0.99, 95% confidence interval (CI) 0.98-0.99) and good interobserver agreement 0.83 [95% CI 0.58-0.94]) on a 1.5 T system for 12 patients with knee osteoarthritis [25]. As for SQ assessment no data has been published specifically assessing reliability on 3 T systems.…”
Section: Discussionmentioning
confidence: 99%
“…A single reader (T.A.P) performed segmentation of STV (mm 3 ) using a semi-automated approach that has been described previously [ 31 ]. In brief, the software segments enhancing STV (on CE-MRI) based on a threshold, as selected by the user, within a 3 D-mask that is applied to the target image [ 31 ]. STV measured across the whole joint was termed total absolute STV (aSTV).…”
Section: Methodsmentioning
confidence: 99%